EVALUATING THE EFFECTIVENESS OF STORY-BASED LEARNING (SBL) IN ENHANCING ENGLISH ACHIEVEMENT AMONG GRADE 4 LEARNERS - Joshua Luis (SEAMEO QITEP in Language, 2026)
This study evaluated the effectiveness of the Story-Based Learning Approach in enhancing English achievement among Grade 4 learners at Banus Elementary School, Oriental Mindoro, Philippines. The study employed a quasi-experimental pretest-posttest control group design involving 48 learners from two intact sections. Twenty-five learners comprised the experimental group, which received instruction through Story-Based Learning, while 23 learners formed the control group, which was taught using conventional English instruction. The intervention integrated storytelling, guided reading, vocabulary enrichment, comprehension activities, collaborative discussion, and reflective tasks. Data were gathered using a researcher-made English Achievement Test based on Grade 4 English competencies. The instrument was validated by five Master Teachers and three School Principals and yielded a test-retest reliability coefficient of 0.87. Descriptive statistics, paired-samples t-tests, an independent-samples t-test, and Cohen’s d were used for analysis. Results showed that both groups improved significantly from pretest to posttest; however, the experimental group obtained a greater mean gain. Its mean score increased from 62.40 to 85.60, whereas the control group’s mean score increased from 61.90 to 74.80. The paired-samples t-test indicated a significant improvement in the experimental group, t(24) = 12.45, p < .001, while the independent-samples t-test revealed a significant difference between the posttest scores of the two groups, t(46) = 5.32, p < .001. Effect size analysis showed a very high practical impact for Story-Based Learning. The findings suggest that Story-Based Learning is an effective instructional intervention for elementary English instruction because it situates vocabulary, comprehension, language use, and classroom interaction within meaningful narrative contexts.